(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
This paper represents a part of an exploratory study on the processes of abductive reasoning as a strategy in foreign language learning, with its possible applications for foreign language instruction. The specific purpose of the study is to explore students’ usage of their plurilingual repertoires through their cognitive thinking system of hypothesis making. Coming from the theory of foreign language acquisition and practice, the main study explores the concept of plurilingualism and investigates the ability of students to use their background knowledge (from mother tongue, second language/s, foreign language/s), and all their past experiences, in order to make conclusions and transform experience into usable information. It is assumed that acquisition of all kinds of knowledge and experiences leads to better anticipation and understanding. Thus, when the language learner is confronted with a new linguistic unit for the first time, he/she uses background information and generates a causal explanation.